The use of names of dishes in modern Turkic languages from the monument of M. Kashgari “Divani lugat it-Turk” - Kossybayev М.М.; Zhiyembay Б.С.; Khalmetov А.Р. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
An important place on the path of the revival of the deeply rooted Turkic civilization is occupied by the study of written monuments representing the history, language, literature, culture, way of life, mythological religious beliefs and material values of the Turkic peoples. Among the topical issues is the comprehensive differentiation of the language of Mahmoud Kashgari’s monument "Divani lugat it-Turk", which is a common heritage not only of Kazakh, but also of all Turkic peoples, the disclosure of the ethnocultural content of linguistic units that reveal the worldview and existence of medieval Turks. The article considers the quantitative and thematic classification of the names of dishes in the work of Mahmoud Kashgari "Divani lugat it-Turk" ("Turkic Dictionary") and examines their etymological basis.